2017
DOI: 10.26911/jepublichealth.2017.02.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis on Life Course Factors Affecting Overweight and Obesity in Children Aged 2 to 5 Years Old in Surakarta

Abstract: Background: Globally, prevalence of obesity in children under 5 years old has been increasing from 32 million in 1990 to 42 million in 2014. Indonesia ranks highest in the number of obesity cases in South East Asia with prevalence of 11.5% in 2013. However, child overweight and obesity have not been the focus of health problems in Indonesia. Early intervention and prevention of child obesity can reduce long-term risk of chronic diseases in adulthood. This study aimed to analyze the life course factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(64 reference statements)
1
0
0
Order By: Relevance
“…The result of this study was in line with Nudhira et al, (2017) which showed that there was a positive and significant effect of maternal body mass index (BMI) on overweight and obese toddlers. Overweight/obesity mothers increase their risk of having offspring with overweight/obesity compared to mothers with normal weight.…”
Section: The Effect Of Parental Income On Fat and Obesitysupporting
confidence: 86%
“…The result of this study was in line with Nudhira et al, (2017) which showed that there was a positive and significant effect of maternal body mass index (BMI) on overweight and obese toddlers. Overweight/obesity mothers increase their risk of having offspring with overweight/obesity compared to mothers with normal weight.…”
Section: The Effect Of Parental Income On Fat and Obesitysupporting
confidence: 86%